2019
DOI: 10.1103/physrevmaterials.3.073401
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of incubation time preceding the Ga-assisted nucleation and growth of GaAs nanowires on Si(111)

Abstract: The incubation time preceding nucleation and growth of surface nanostructures is interesting from a fundamental viewpoint but also of practical relevance as it determines statistical properties of nanostructure ensembles such as size homogeneity. Using in situ reflection high-energy electron diffraction, we accurately deduce the incubation times for Ga-2 assisted GaAs nanowires grown on unpatterned Si(111) substrates by molecular beam epitaxy under different conditions. We develop a nucleation model that expla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…At time t = 0 seconds, WZ and ZB IRs are equal to 0.5, due to the absence of NWs (the measured intensities are those measured on the diffraction line of the Si(111) substrate surface). Once the Ga and As fluxes are opened, an increase of the ZB IR (correspondingly, a decrease of the WZ IR ) is observed due to the growth of the parasitic ZB GaAs nanocrystals during the first few seconds, and then due to the nucleation and the growth of the NWs after a few tens of seconds 38 (zone (i 1 )). After 90 seconds, we observe a short and slight decrease of the ZB IR (correspondingly, a short and slight increase of the WZ IR) for about 40 seconds (zone (i 2 )).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At time t = 0 seconds, WZ and ZB IRs are equal to 0.5, due to the absence of NWs (the measured intensities are those measured on the diffraction line of the Si(111) substrate surface). Once the Ga and As fluxes are opened, an increase of the ZB IR (correspondingly, a decrease of the WZ IR ) is observed due to the growth of the parasitic ZB GaAs nanocrystals during the first few seconds, and then due to the nucleation and the growth of the NWs after a few tens of seconds 38 (zone (i 1 )). After 90 seconds, we observe a short and slight decrease of the ZB IR (correspondingly, a short and slight increase of the WZ IR) for about 40 seconds (zone (i 2 )).…”
Section: Resultsmentioning
confidence: 99%
“…Scarpellini et al 24 reported on the consumption of the Ga droplets at the end of the growth, while Rudolph et al 21 reported on the influence of the As flux on the InAs NW structural properties and Bastiman et al reported on the incubation time of GaAs NWs. 38 Only recently, in situ RHEED characterization of the NW growth coupled with ex situ TEM measurements was reported by Jo et al 39 …”
Section: Introductionmentioning
confidence: 99%
“…To date only a few studies report on the use of the RHEED for the growth of self-assisted GaAs NWs. For instance, RHEED has only been used to investigate the consumption of the catalyst droplet at the end of the growth 25 , while Bastiman et al reported on the incubation time for the growth of the GaAs NWs 26 . The use of RHEED as an in situ characterization tool of the growth of NWs coupled with numerical simulations has been reported recently by Jakob et al 27 In this work, we achieve the growth of self-assisted GaAs NWs with an extended pure WZ segment, controlled by in situ RHEED and based on simulations.…”
Section: Introductionmentioning
confidence: 99%